Faktor-faktor yang Mempengaruhi Volume Penjualan Pakan Ternak di PT Japfa Comfeed Indonesia, Tbk. Unit Makassar - Aisyah, Aisyah; Sari, Anita; Azis, Winda Ariyanti (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Product sales strategies are supported by technology that makes it easy for consumers to buy a product. According to Sulastri (2014) sales volume is the level of sales obtained by the company for a certain period in units (units/total/rupiah). The purpose of this study was to determine what are the factors that affect the sales volume of animal feed at PT. Japfa Comfeed Indonesia, Tbk. Makassar Unit. Feed is a single or mixed food material, both processed and unprocessed, which is given to animals for survival, reproduction and breeding. This research was conducted in April and July 2023, which took place at PT Japfa Comfeed Indonesia. Based on this, this research uses qualitative data so that in collecting data interviews with 30 respondents are conducted. The results of this study indicate that when viewed simultaneously or as a whole the factors that affect the sales volume of animal feed at PT. Japfa Comfeed Indonesia, Tbk. Makassar Unit, namely demand and supply, fluctuating feed prices, upward trends in raw material prices, and demand on holidays. However, after several data analysis tests, only demand and supply and the trend of rising raw material prices have a very strong (significant) influence on the volume of animal feed sales.